ON IDENTIFICATION OF VARIABLE RIGIDITY UNDER THE ANALYSIS OF THE BEAN LATERAL OSCILLATION - Alexander O. VATULYAN; Alisa Y. BURYAN; Alexey V. OSIPOV (Advanced Engineering Research)
The method of amplitude characteristic estimation for the cantilever bean of the variable rigidity on the basis of the analysis of Fredholm integral equation of the second kind is presented. The determination method of rigidity changing on the basis of Cauchy sequence analysis.